2022
DOI: 10.1002/ccr3.5389
|View full text |Cite
|
Sign up to set email alerts
|

Ectopia cordis in an adult patient with COVID‐19: A case report and literature review

Abstract: Ectopia cordis (EC) is a rare congenital condition characterized by a partial or complete defect of the anterior chest wall. It is associated with ventricular and atrial septal defects (ASD), Ebstein's anomaly, truncus arteriosus, transposition of the great vessels, tetralogy of Fallot, and hypoplastic left heart syndrome. This study aimed to explore the cardiac manifestations of EC complicated by coronavirus disease 2019 (COVID‐19). A 23‐year‐old male, born with EC, was admitted to the hospital for acute coug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Lastly, in the same year, Kebalo et al in the Togolese Republic reported a case of midsternal defect of ectopia cordis and the newborn expired 22 hours after birth which also made them unable to perform any procedure [ 29 ]. The most recent case reported in the year 2022 from Saudi Arabia by Alshamiri et al was a case of incomplete ectopia cordis in a 23-year-old male, who expired due to COVID-19 infection [ 30 ]. This last patient might indicate that in patients with incomplete or partial ectopia cordis, survival may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, in the same year, Kebalo et al in the Togolese Republic reported a case of midsternal defect of ectopia cordis and the newborn expired 22 hours after birth which also made them unable to perform any procedure [ 29 ]. The most recent case reported in the year 2022 from Saudi Arabia by Alshamiri et al was a case of incomplete ectopia cordis in a 23-year-old male, who expired due to COVID-19 infection [ 30 ]. This last patient might indicate that in patients with incomplete or partial ectopia cordis, survival may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that the cardiac anomaly has priority over the surgical treatment of the omphalocele, and after covering the pericardial defect and closing the chest wall defect, the management of the case will be established according to the cardiac structural anomalies. The prognosis is usually poor, but patients may survive to adulthood if they have an incomplete EC, fewer intracardiac defects except for ASD, and absence of an omphalocele [ 32 ].…”
Section: Omphalocele Patients With Cardiac Abnormalitiesmentioning
confidence: 99%